The impact of telemedicine on pediatric type 1 diabetes management: benefits, challenges, and future directions - Esposito, Susanna; Sambati, Vanessa; Fogliazza, Federica; Street, Maria Elisabeth; Principi, Nicola (Frontiers in Endocrinology, 2024)
Telemedicine (TM) has emerged as a valuable tool in managing pediatric type 1 diabetes (T1D), particularly during the COVID-19 pandemic when traditional in-person visits were limited. This narrative review examines the impact of TM on patient-provider relationships, glycemic control, and overall diabetes management in children and adolescents with T1D. Studies consistently demonstrate high levels of patient and provider satisfaction with TM, citing increased consultation frequency, reduced travel burdens, and lower associated costs. However, results regarding the effect of TM on glycemic control, as measured by HbA1c levels, are inconsistent. Some studies show significant reductions in HbA1c levels with TM use, while others report outcomes comparable to or less effective than traditional care. The effectiveness of TM also appears to be influenced by the concurrent use of advanced diabetes technologies, such as continuous glucose monitors and automated insulin delivery systems. Furthermore, TM’s impact on quality of life and other clinical outcomes beyond glucose management remains underexplored. Methodological limitations, including inconsistent randomization strategies and lack of long-term follow-up, hinder definitive conclusions. Despite these uncertainties, TM offers several advantages, such as improved accessibility and patient engagement, which may justify its broader implementation. Future research should focus on optimizing TM approaches to enhance glycemic control and quality of life, identifying the most effective strategies for specific patient groups, and addressing technological and economic barriers. This review highlights the need for comprehensive, long-term studies to fully understand TM’s potential in pediatric T1D management and its integration into standard care practices.